The urban risk assessment: a methodological proposal - Maragno, Denis; Musco, Francesco (AESOP, 2017)
The risks for cities and natural environment coming from the climate change seems to give back substance to the considerations on urban sustainability, a word rich in promises, but poor in applicative content. The Global Risks Report 2016 considers all the possible potential impacts on global scale, measured in a Cartesian system. In the diagram, the x-axis defines the probability of occurrence, and the yaxis shows the impact degree on economies, population and environment. The highest position, caused by a high probability and a devastating impact on world scale represents a failure of adaptation and mitigation policies. Then the migration caused by wars and environment disasters follows, and the third position is assigned to water scarcity (both attributable to the climate change consequences). Today the challenge of climate change represents one of the most complex scientific and political questions of the 21th century. International institutions like IPCC, OCSE, FAO, UNDP, just to mention a few, identify climate externalities like extreme rainfalls, heat and drought waves as scenarios of high environmental impact for the next 100 years. The worst-case scenarios in economic and human life terms will occur above all in the cities (Betsill, Bulkeley, 2005; Biesbroek, Swart, van der Knaap, 2009; Van der Veen, Spaans, Putters, Janssen-Jansen 2010). The climate change topic enters local political agendas, pushed by the urgency perceived on an international level, though finding difficulties in application.
Book of proceedings: Annual AESOP Congress, Spaces of Dialog for Places of Dignity, Lisbon, 11-14th July, 2017